Advancing Gender Inclusion in Engineering: Systematic Review of Educational and Institutional Strategies - Ramos-Zaga, Fernando (LACCEI, 2025)
In recent decades, engineering has served as a strategic pillar for technological advancement and global development. However, its transformative potential remains constrained by a persistent gender gap that limits women’s participation. Numerous studies have documented the existence of systemic barriers, including gender stereotypes, the absence of female professional role models, and restrictive sociocultural norms, all of which negatively affect women’s access, retention, and professional advancement in this field. Against this backdrop, the present study aims to analyse the main obstacles hindering women’s participation in engineering careers by identifying and synthesizing the social, educational, and cultural factors contributing to this disparity. To this end, a systematic literature review was conducted following the PRISMA protocol, based on searches in the Scopus, Web of Science, and IEEE Xplore databases. The inclusion criteria focused on empirical studies published between 2019 and 2024 that address women’s participation in engineering from social and educational perspectives. After applying rigorous selection filters, 46 articles were included for analysis. The findings indicate that gender stereotypes, biased pedagogical practices, the limited visibility of female role models, and exclusionary institutional dynamics remain key determinants of the underrepresentation of women in engineering. Consequently, the study underscores the need for structural transformations in both educational systems and professional environments to foster equitable conditions that enable the full and sustained participation of women in this field.